Climate and management interact to explain the decline of woodland caribou (Rangifer tarandus caribou) in Jasper National Park - Bradley, Mark; Neufeld, Lalenia (Rangifer, 2012)
Woodland caribou in the southern portion of Jasper National Park have declined from an estimated 435 in the mid 1970s to a population estimate of 87 in the fall of 2009. We examined the available historical information to determine why caribou have declined. We compared three main hypotheses for caribou decline in JNP: human disturbance, climate change, and wildlife management. We used historical human use statistics, climate data, and animal abundance information to weigh the evidence for these competing hypotheses over two time scales. Caribou decline could not be attributed to changes in climate over the long-term, or an increase in human use (our proxy for disturbance). Caribou decline was attributed to a combination of climate and wildlife management. Recovery of caribou in Jasper National Park will likely be contingent on managing the interaction between the predator/prey dynamic and climate change.